2016
DOI: 10.1128/aac.00727-15
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Ceftolozane plus Tazobactam Studied in an In Vitro Pharmacokinetic Model of Infection

Abstract: Ceftolozane plus tazobactam is an antipseudomonal cephalosporin combined with tazobactam, an established beta-lactamase inhibitor, and has in vitro potency against a range of clinically important ␤-lactamase-producing bacteria, including most extended-spectrum-␤-lactamase (ESBL)-positive Enterobacteriaceae. The pharmacodynamics of ␤-lactam-␤-lactamase inhibitor combinations presents a number of theoretical and practical challenges, including modeling different half-lives of the compounds. In this study, we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Similar results were recently obtained in an in vitro pharmacokinetic model of infection, against both E. coli and P. aeruginosa [57]. The %T>MIC for 1-log and 2-log decrease in initial inoculum for E.coli were 33.0% and 39.6%, respectively, and CTX-M-15 production did not affect this pharmacodynamic index [57]. For P. aeruginosa, the %T>MIC for 1-log and 2-log decrease in initial inoculum were 26.6% and 31.2%, respectively [57].…”
Section: Pharmacodynamicssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were recently obtained in an in vitro pharmacokinetic model of infection, against both E. coli and P. aeruginosa [57]. The %T>MIC for 1-log and 2-log decrease in initial inoculum for E.coli were 33.0% and 39.6%, respectively, and CTX-M-15 production did not affect this pharmacodynamic index [57]. For P. aeruginosa, the %T>MIC for 1-log and 2-log decrease in initial inoculum were 26.6% and 31.2%, respectively [57].…”
Section: Pharmacodynamicssupporting
confidence: 88%
“…In the same study, it was shown that ceftolozane had faster rate of in vivo killing of P. aeruginosa A c c e p t e d M a n u s c r i p t than ceftazidime, and that the most potent combination with tazobactam against ESBLproducing Enterobacteriaceae could be obtained using a 2:1 ratio (2000 mg of ceftolozane and 1000 mg of tazobactam) [56]. Similar results were recently obtained in an in vitro pharmacokinetic model of infection, against both E. coli and P. aeruginosa [57]. The %T>MIC for 1-log and 2-log decrease in initial inoculum for E.coli were 33.0% and 39.6%, respectively, and CTX-M-15 production did not affect this pharmacodynamic index [57].…”
Section: Pharmacodynamicssupporting
confidence: 80%
See 1 more Smart Citation
“…Optimal drug doses were defined as the smallest practical daily dose resulting in at least 90% of the 5,000 virtual patients attaining a predetermined pharmacodynamic target of a free ceftolozane serum concentration above the minimum inhibitory concentration (MIC) of 4 mg/L (fT/MIC) for ≥60% of the dosing interval versus Pseudomonas aeruginosa during the initial 48 h of treatment [24,25]. Given that tazobactam has no activity against Pseudomonas aeruginosa , the target of a free tazobactam serum concentration above an MIC of 2 mg/L for ≥50% of the dosing interval for Enterobacteriaceae was used [25,26,27,28,29]. This >50% fT/MIC threshold is based on in vitro infection models that indicated good correlation between fT/MIC for 50% of a dosing interval and reduction in colony forming units over 24 h [29].…”
Section: Methodsmentioning
confidence: 99%
“…Ceftolozane-tazobactam (Zerbaxa TM ) pairs a novel anti-pseudomonas cephalosporin with the beta-lactamase inhibitor tazobactam [101]. Ceftolozane-tazobactam's spectrum of activity also includes ESBL producing organisms.…”
Section: New Therapeutics In Resistant Gram-negative Infectionsmentioning
confidence: 99%